2020
DOI: 10.1007/s12517-020-05915-5
|View full text |Cite
|
Sign up to set email alerts
|

Hazard, ecological, and human health risk assessment of heavy metals in street dust in Dezful, Iran

Abstract: This study aimed to investigate the potentially toxic metal (Pb, Zn, Cu, Cr, Cd, Ni, V, As, and Co) hazard in street dust from Dezful, Iran. For this purpose, we collected 30 samples of street dust from the main pedestrian sidewalks of Dezful. Subsequent heavy metal concentration data for these samples was evaluated using human health risk and potential ecological risk index (RI) assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2121
2121

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 44 publications
1
7
1
Order By: Relevance
“…The value of the Pb concentration in street dust (52.2 mg/kg) was similar to the values reported by previous studies from Dezful, Iran (54 mg/kg) [16], Abu Dhabi-Al Ain National highway, UAE (50.1 mg/kg) [11], and Beijing, China (62.3 mg/kg) [5]. On the other hand, higher levels of Pb were also found in other studies, for instance, in Nanchang, China (89.5 mg/kg) [4], Xi'an, China (94.5 mg/kg) [3], Jinhua, China (110.6 mg/kg) [6], and Tianjin, China (120.7 mg/kg) [13].…”
Section: Basic Statistics Of Metals Concentrationsupporting
confidence: 89%
See 3 more Smart Citations
“…The value of the Pb concentration in street dust (52.2 mg/kg) was similar to the values reported by previous studies from Dezful, Iran (54 mg/kg) [16], Abu Dhabi-Al Ain National highway, UAE (50.1 mg/kg) [11], and Beijing, China (62.3 mg/kg) [5]. On the other hand, higher levels of Pb were also found in other studies, for instance, in Nanchang, China (89.5 mg/kg) [4], Xi'an, China (94.5 mg/kg) [3], Jinhua, China (110.6 mg/kg) [6], and Tianjin, China (120.7 mg/kg) [13].…”
Section: Basic Statistics Of Metals Concentrationsupporting
confidence: 89%
“…The highest Cr concentration was obtained in sample D4 (123.6 mg/kg), while the lowest value was observed in sample D2 (51.3 mg/kg). These values were higher than those previously reported from Asaluyeh County, Iran (37.3 mg/kg) [17], the Lagos metropolis, Southwestern Nigeria (41.3 mg/kg) [53], and Dezful, Iran (44 mg/kg) [16].…”
Section: Basic Statistics Of Metals Concentrationcontrasting
confidence: 70%
See 2 more Smart Citations
“…The results revealed that the mean concentration of all studied PTEs in the study area was higher than the local baseline, Upper Continental Crust (UCC), world soil, Canadian, Dutch, and Chinese soil quality guidelines. However, this finding suggests the anthropogenic source of the PTEs, such as vehicle traffic emissions, industrial inputs, construction, and steel industry [22,23]. The Kolmogorov-Smirnov results showed that the concentration of the studied PTEs had a nonnormal distribution behavior (Sig.…”
Section: Resultsmentioning
confidence: 88%